2017
DOI: 10.1016/j.scitotenv.2017.02.034
|View full text |Cite
|
Sign up to set email alerts
|

A tool for cost-effectiveness analysis of field scale sediment-bound phosphorus mitigation measures and application to analysis of spatial and temporal targeting in the Lunan Water catchment, Scotland

Abstract: The cost-effectiveness of six edge-of-field measures for mitigating diffuse pollution from sediment bound phosphorus (P) runoff from temperate arable farmland is analysed at catchment/field scales. These measures were: buffer strips, permanent grassland in the lowest 7% of arable fields, dry detention bunds, wetlands, and temporary barriers such as sediment fences. Baseline field P export was estimated using export coefficients (low risk crops) or a modified Universal Soil Loss Equation (high risk crops). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In isolating the limiting nutrient (and form thereof) and prioritising areas that require remediation, the choice and cost-effectiveness of good management practices can be optimised 56 . Once land managers know which nutrient to concentrate on they can identify small areas of the farm, often term critical source areas, that account for the majority of losses to water 57 .…”
Section: Discussionmentioning
confidence: 99%
“…In isolating the limiting nutrient (and form thereof) and prioritising areas that require remediation, the choice and cost-effectiveness of good management practices can be optimised 56 . Once land managers know which nutrient to concentrate on they can identify small areas of the farm, often term critical source areas, that account for the majority of losses to water 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Transforming this knowledge into appropriate cost effective mitigation strategies remains a major challenge (Schoumans et al, 2014(Schoumans et al, , 2015Dodds and Sharpley, 2015;Kleinman et al, 2015;Sharpley et al, 2015;Withers et al, 2015a,b;Rowe et al, 2016). The degree of integration and knowledge is such today that some of the most recent studies can go as far as integrating the costs of management in the reduction of diffuse phosphorus emissions, in connection with national or local legislation or land property issues (e.g., McDowell et al, 2016;Vinten et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…, Vinten et al. ). McDowell () showed that across 14 sub‐catchments farmed with sheep, red deer, beef, or dairy cattle, the cost‐effectiveness of mitigations targeted to critical source areas was six to seven times higher than untargeted mitigation actions.…”
Section: Factors To Consider When Choosing Management Actionsmentioning
confidence: 99%
“…, Vinten et al. ). Furthermore, although proxies such as connectivity indices exist to indicate the likely response time of actions, direct evidence of treatment speeds is sparse (Stieglitz et al.…”
Section: Introductionmentioning
confidence: 99%